2017
DOI: 10.1016/j.algal.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phenotype stability and ecological risk of a genetically engineered alga in open pond production

Abstract: A B S T R A C TGenetically engineered (GE) algae offer the promise of producing food, fuel, and other valuable products with reduced requirements for land and fresh water. While the gains in productivity measured in GE terrestrial crops are predicted to be mirrored in GE algae, the stability of phenotypes and ecological risks posed by GE algae in large-scale outdoor cultivation remain unknown. Here, we describe the first US Environmental Protection Agency (EPA)-sanctioned experiment aimed at understanding how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…In addition to phenotype stability in outdoor conditions, the ecological risk due potential accidental environmental releases of genetically engineered microalgae/cyanobacteria has emerged as a major concern during large-scale cultivation [54,55]. Evaluation in open pond production systems represent a crucial step in understanding potential ecological risk of genetically engineered cyanobacteria/microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to phenotype stability in outdoor conditions, the ecological risk due potential accidental environmental releases of genetically engineered microalgae/cyanobacteria has emerged as a major concern during large-scale cultivation [54,55]. Evaluation in open pond production systems represent a crucial step in understanding potential ecological risk of genetically engineered cyanobacteria/microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…While there are currently limited studies on genetic engineering of microalgae for bioremediation purposes, Chiaiese et al (2011) successfully demonstrated fungal laccase POX A1b expression in the green alga, Chlorella emersonii, which enhanced microalgal biodegradation of phenols by up to about 40%. However, while genetically engineering microalgae for enhanced biodegradation appears promising, the potential environmental risks intrinsic to the use of genetically modified organisms (GMO) that would limits their application in outdoors settings need to be evaluated (Szyjka et al, 2017). In addition to this, for many countries, the legislation around the limited use, or the total ban of, GMOs means that transgenic microalgae for ECs biodegradation would not be a viable option, at present.…”
Section: Algal Biodegradation Of Emerging Contaminantsmentioning
confidence: 99%
“…EFSA reviewed this area and commented as follows: “According to our experience, the current European legislative framework for GMOs and for food/feed products of microbial origin (whether they are GM or not) would cover GM microalgae sufficiently.” Regardless of the category of organism, the regulations considered herein relate to GMOs broadly and would include both GMMs and GM Plants. With regard to production of GM algae beyond labscale, contained use—often double-contained or restricted-access greenhouse—is considered to be a safe working model at the current time, although outdoor trials have gone ahead and have been reported in the USA [ 29 ].…”
Section: Gene Editing In Algae: Current State Of the Artmentioning
confidence: 99%